2018
DOI: 10.1109/tthz.2017.2775445
|View full text |Cite
|
Sign up to set email alerts
|

THz Imaging System for in vivo Human Cornea

Abstract: Terahertz (THz) imaging of corneal tissue water content (CTWC) is a proposed method for early, accurate detection and study of corneal diseases. Despite promising results from and cornea studies, interpretation of the reflectivity data is confounded by the contact between corneal tissue and rigid dielectric window used to flatten the imaging field. This work develops a novel imaging system and image reconstruction methods specifically for nearly spherical targets such as human cornea. A prototype system was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 12 publications
1
41
0
Order By: Relevance
“…In more complicated models, the diffusion of water could be considered in both the axial and the perpendicular directions. Future work will include expanding our model to include diffusion in the perpendicular directions and tracking it using spatial mapping of a spherical target, based on the experimental techniques in [16,17]. Furthermore, these results can be generalized to other tissue types or non-biological samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In more complicated models, the diffusion of water could be considered in both the axial and the perpendicular directions. Future work will include expanding our model to include diffusion in the perpendicular directions and tracking it using spatial mapping of a spherical target, based on the experimental techniques in [16,17]. Furthermore, these results can be generalized to other tissue types or non-biological samples.…”
Section: Discussionmentioning
confidence: 99%
“…The high homogeneity and relatively low physiological variability of corneal tissue make THz radiation a fitting tool for hydration measurements [5,6,[12][13][14][15][16]. In addition to a sensitivity analysis, the study by Taylor et al showed the feasibility of THz imaging for cornea analysis by performing in vivo experiments on dehydrating healthy rabbit corneas through a mylar window [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principle has been verified through the experimental results on ex-vivo porcine corneas [21,22] and in-vivo studies of rabbits [23] and humans [24]. By scanning a focused THz beam on volunteer's eye, Sung S., et al have obtained the reflectivity maps which represent spatial hydration distribution across human cornea [25][26][27]. But the reflected signal intensity is susceptible to all sorts of factors arising from instruments and samples, which will limit the accuracy and repeatability of measurements and make it challenging to calibrate the relation between CTWC and THz reflectivity.…”
Section: Introductionmentioning
confidence: 88%
“…[5][6][7][8] In biomedical applications these technologies are frequently used for breast cancer diagnostics both in preclinical research settings as well as in the clinical assessment of patients, [9][10][11][12] though they can be applied for a number of other biomedical tasks. 13,14 Because of the relatively large width of the THz spectra THz radiation is of great importance in terms of fundamental researches as well as in technology and life sciences, as in this region rotational and vibrational lines of a lot of substances are located e.g. of molecules like proteins or DNA.…”
Section: Introductionmentioning
confidence: 99%